CEO overseas experiences and corporate financialization: evidence from China - Zheng, Minyu; Mohd Nor, Normaziah; Mohd Ashhari, Zariyawati (The Brooklyn Research and Publishing Institute, 2024)
Recently, Chief Executive Officers (CEOs) with overseas experiences have shown the ―star effect‖, according to upper echelons theory, CEOs’ overseas experiences might relate to corporate financialization, but there is little evidence of whether and how CEOs’ overseas experiences affect it. Given the increasing trend of hiring overseas CEO’s in China, the study fills in the gap in the literature by examining the effect of CEOs with overseas experiences on corporate financialization. In sum, the study employs a two-way fixed effect model to investigate the relationship between CEOs with overseas experiences and corporate financialization, a conclusion that remains valid after a series of robustness tests. CEOs with overseas experiences primarily inhibit corporate financialization by alleviating financing constraints and improving investment efficiency. Furthermore, the study finds that compared to overseas work experience, overseas study experience has a more pronounced inhibitory effect on corporate financialization. Female CEOs and young CEOs with overseas experiences exhibit a more significant inhibitory effect on corporate financialization. Cross-sectional tests show that the inhibitory effects are more pronounced in SOEs and non-polluting industries and the eastern regions, especially in the highly marketized provinces in China.